2019
DOI: 10.1038/s41598-019-52407-y
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Stiffness as Predictor of Esophageal Varices in Cirrhosis of Different Etiologies

Abstract: The purpose of this study is to determine whether esophageal varices (EV) can be identified through the evaluation of spleen stiffness (SSM) via acoustic radiation force impulse (ARFI). A total of 135 patients suffering from cirrhosis underwent a clinical exam, laboratory tests, abdominal ultrasound, liver stiffness (LSM) measurement, SSM evaluation and upper gastrointestinal endoscopy. Based on the endoscopy results, the patients were classified into three groups: those with no evident EV, those with small EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…As it was already shown in other studies [ 10 , 32 34 ], in our group, the mean SSM values determined by both techniques were significantly higher for patients with VNT as compared to those without. The diagnostic accuracy of SSM by both p-SWE and 2D-SWE for predicting the presence of VNT was evaluated and good diagnostic accuracy was found (AUROC 0.90 and 0.84, resp.…”
Section: Discussionsupporting
confidence: 89%
“…As it was already shown in other studies [ 10 , 32 34 ], in our group, the mean SSM values determined by both techniques were significantly higher for patients with VNT as compared to those without. The diagnostic accuracy of SSM by both p-SWE and 2D-SWE for predicting the presence of VNT was evaluated and good diagnostic accuracy was found (AUROC 0.90 and 0.84, resp.…”
Section: Discussionsupporting
confidence: 89%
“…Attempts have been made to use less invasive modalities as an alternative tool for the stratification of GEVs [4, 13,14]. Spleen stiffness accurately reflects the severity of portal hypertension and is effective in EV prediction [15,16]. A recent study developed a model with spleen stiffness assessed by point-shear-wave elastography, and it provides accurate information in cirrhotic patients for excluding endoscopy requirements [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored SSM in the prediction of EV[ 40 , 44 - 47 ]. A prospective study of 135 patients demonstrated that patients with any EV had higher SSM than those with no EV (3.37 m/s vs 2.79 m/s, P < 0.001); and patients with HREV had an even greater difference in SSM (3.96 m/s vs 2.93 m/s, P < 0.001)[ 44 ]. In addition, at a cutoff value of < 3.20 m/s, NPV for excluding HREV was 99%[ 44 ].…”
Section: Spleen Stiffness Measurementmentioning
confidence: 99%
“…A prospective study of 135 patients demonstrated that patients with any EV had higher SSM than those with no EV (3.37 m/s vs 2.79 m/s, P < 0.001); and patients with HREV had an even greater difference in SSM (3.96 m/s vs 2.93 m/s, P < 0.001)[ 44 ]. In addition, at a cutoff value of < 3.20 m/s, NPV for excluding HREV was 99%[ 44 ]. SSM was therefore evaluated in 2 prospective studies and demonstrated good diagnostic accuracy for prediction of any EV, with AUROC of 0.872 to 0.933 at a cutoff of 2.89-3.18 m/s, and good diagnostic accuracy for the prediction of HREV, with AUROC of 0.930–0.969 at cutoffs of 3.30 m/s[ 45 , 47 ].…”
Section: Spleen Stiffness Measurementmentioning
confidence: 99%